2018
DOI: 10.3126/jucms.v5i2.19155
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Laboratory Observations and Outcome of Dengue Infection In a Tertiary Care Hospital of Western Nepal: An Observational Cross-Sectional Study

Abstract: INTRODUCTION: Dengue fever (DF) is highly prevalent in tropical and subtropical countries all over the world. This study was done to study the clinico-laboratory profile of DF patients and their outcomes in a tertiary care hospital of western Nepal.MATERIAL & METHODS:  A prospective observational cross-sectional study conducted over 6 months (October 2016 to March 2017) in patients admitted to medical inpatient ward of a tertiary care referral hospital located at south west Nepal. All febrile patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…Another study carried out by HOSSAIN MZ et al reported more cases of dengue infection in males as compared to females 8 . Another study carried out by Jaiswal N et al reported that dengue infection occurs more in females as compared to males which in concordance to our findings 14 . The socio-cultural context of that area may have contributed to these inconsistent results.…”
Section: Discussionsupporting
confidence: 93%
“…Another study carried out by HOSSAIN MZ et al reported more cases of dengue infection in males as compared to females 8 . Another study carried out by Jaiswal N et al reported that dengue infection occurs more in females as compared to males which in concordance to our findings 14 . The socio-cultural context of that area may have contributed to these inconsistent results.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, prevalence of dengue is three times higher in male gender. The finding is similar to findings to other study in home and abroad 5,8 . However, a recent publication from western Nepal by N. college et al found that females infected more than males 8 .…”
Section: Discussionsupporting
confidence: 92%
“…The finding is similar to findings to other study in home and abroad 5,8 . However, a recent publication from western Nepal by N. college et al found that females infected more than males 8 . Sociocultural background of that region might have play a role for this dissimilar findings.…”
Section: Discussionsupporting
confidence: 92%